Upper extremity ischemia is superior to lower extremity ischemia for remote ischemic conditioning of antero–lateral thigh cutaneous blood flow. Issue 3 (3rd October 2014) - Kolbenschlag, J.; Sogorski, A.; Harati, K.; Daigeler, A.; Wiebalck, A.; Lehnhardt, M.; Kapalschinski, N.; Goertz, O.
Abstract : Remote ischemic conditioning (RIC) is known to improve microcirculation in various settings, but little is known about the impact of the amount of ischemic tissue mass or the limb itself. Since ischemia and subsequent necrosis of flaps is one of the most dreaded complications in reconstructive surgery, adjuvant methods to improve microcirculation are desirable. We therefore performed a randomized trial to compare the effect of arm versus leg ischemia for RIC of the cutaneous microcirculation of the antero–lateral thigh. Forty healthy volunteers were randomized to undergo 5 min of ischemia of either the upper or lower extremity, followed by 10 min of reperfusion.Ischemia was induced by a surgical tourniquet applied to the proximal limb, which was inflated to 250 mmHg for the upper and 300 mgHg for the lower extremity. This cycle was repeated a total of three times. Cutaneous microcirculation was assessed by combined laser doppler spectrophotometry on the antero–lateral aspect of the thigh to measure cutaneous blood flow (BF), relative hemoglobin content (rHb), and oxygen saturation (StO2). Baseline measurements were performed for 10 min, after which the ischemia/reperfusion cycles were begun. Measurements were performed continuously and were afterwards pooled to obtain a mean value per minute. Both groups showed significant increases in all three measured parameters of cutaneous microcirculation after three cycles of ischemia/reperfusion when compared to baseline (BF: 95.1% ( P  < 0.001) and 27.9% ( P  = 0.002); rHb: 9.4% ( P  < 0.001) and 5.9% ( P  < 0.001), StO2: 8.4% ( P  = 0.045) and 9.4% ( P  < 0.001). When comparing both groups, BF was significantly higher in the arm group ( P  = 0.019 after 11 min., P  = 0.009 after 45 min). In conclusions, both ischemic conditioning of the upper and lower extremity is able to improve cutaneous BF on the ALT donor site. However, RIC of the upper extremity seems to be a superior trigger for improvement of cutaneous BF. © 2014 Wiley Periodicals, Inc. Microsurgery 35:211–217, 2015.